2019
DOI: 10.2147/ott.s218043
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-29a function as tumor suppressor in cervical cancer by targeting SIRT1 and predict patient prognosis</p>

Abstract: IntroductionCervical cancer is the second most frequently malignant tumors in females and metastasis is a challenge of the treatment of cervical cancer. MiR-29a is usually low expressed in several tumors and its functions in cervical cancer remain unclear.Patients and methodsThe quantitative real-time polymerase chain reaction was employed to assess the expression of miR-29a and the Sirtuin-1 (SIRT1). Cell metastatic ability was assessed using Transwell and Western blot assays. The dual-luciferase reporter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…In this study, PPI analysis in silico shows that physical interaction is the primary relationship between GSK3β and SIRT1. In contrast, Nan et al has demonstrated that SIRT1 expression level can be regulated by direct binding of miR-29a on its 3 UTR in cervical cancer cells [43]. As such, whether SIRT1 expression targeted by miR-29a underpins the molecular mechanism in hepatocytes and liver of NASH model requires further study for clarification.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, PPI analysis in silico shows that physical interaction is the primary relationship between GSK3β and SIRT1. In contrast, Nan et al has demonstrated that SIRT1 expression level can be regulated by direct binding of miR-29a on its 3 UTR in cervical cancer cells [43]. As such, whether SIRT1 expression targeted by miR-29a underpins the molecular mechanism in hepatocytes and liver of NASH model requires further study for clarification.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, other studies have shown that miR-29a was down-regulated and inhibited the progression of cancers such as colon cancer ( Shi et al, 2020 ), non-small cell lung cancer ( Hu et al, 2016 ) and adenocarcinoma ( Zhang et al, 2018 ). Previous studies have shown that miR-29a was low expression in cervical cancer, as a tumor suppressor, miR-29a can target multiple genes, such as CDC42, HSP47, SIRT1 and DNMT1 ( Park et al, 2009 ; Yamamoto et al, 2013 ; Gong et al, 2019 ; Nan et al, 2019 ). Nonetheless, the detailed biological function of miR-29a in cervical cancer has not yet been completely revealed.…”
Section: Discussionmentioning
confidence: 99%
“…In association with CIN2-3 and cervical carcinoma, several further miRNAs showing dysregulated expression have been reported, such as miR-218, 29a, −101, −140-5p [40][41][42][43][44]. In the study of Gocze et al (2015), progressively increased expression of miR-27a was demonstrated in CIN2-3 as compared to CIN1 and in squamous cell carcinoma (SCC) as compared to CIN2-3, while the levels of miR-34a were found to be lower in CIN2-3 when compared to CIN1 and in SCC in comparison to CIN2-3.…”
Section: Discussionmentioning
confidence: 99%